Understanding Research Data Repositories as Infrastructures. Issue 1 (13th October 2021) - Boyd, Ceilyn
Abstract: This study discusses the properties of research data repositories and explores metadata about 2, 646 entries in the Registry of Research Data Repositories (re3data.org ) to identify the characteristics attributed to infrastructures they exhibit. The results reveal how research data repositories function as information infrastructure for scientific community members and contribute to the small body of literature that examines data repositories through a socio‐technical lens.